Factors Related Health Status Among Pregnant Women With Confirmed Covid-19 In South Sulawesi, Indonesia - Erfina Erfina; Suni Hariati; Kusrini Semarwati Kadar; Numaulid Nurmaulid; Andriani Andriani ((JKG) Jurnal Keperawatan Global, 2022)
Background: Pregnant women are a vulnerable population to COVID-19 due to the high pathogenesis of the disease and its effects on pregnancy. Various studies have been conducted regarding pregnant women during the COVID-19 pandemic. However, limited studies regarding health status of pregnant women with confirmed COVID-19. This study was to identify factors related health status among pregnant women with confirmed COVID-19 in South Sulawesi. Methods: Quantitative study with Cross Sectional design was conducted in this study. The sampling technique was non-probability sampling with a total sample of 37 pregnant women who were confirmed to be COVID-19. Data collection using google forms and data collection entry points from several health centers in Makassar. This variable evaluated with questionnaire by asking what the treatment status when confirmed COVID-19 (hospitalized or quarantine at home). The explanatory variable was maternal age, gestational age at confirmed COVID-19, parity, occupation, family income, frequency of confirmed COVID-19 and those variables were assessed by questionnaire. Bivariate analysis was analyzed using Chi-Square. Results: There was significant correlation between gravidity with health status among pregnant women with confirmed COVID-19 (P=0.040, OR=4.667, 95%CI ). There were no significant correlation between education, employment status, type of employment, and family income with health status among pregnant women with confirmed COVID-19 (P=0.19, P=0.19, P=0.793, P=0.503, 95%CI ). Conclusion: Identification of factors and descriptions of pregnant women with confirmed COVID-19 is important to provide an overview to nurses and other health workers as early detection and efforts to provide interventions to improve maternal and fetal outcomes.